Vascular ADAM17 (a Disintegrin and Metalloproteinase Domain 17) Is Required for Angiotensin II/β-Aminopropionitrile–Induced Abdominal Aortic Aneurysm. Issue 5 (November 2017) - Kawai, Tatsuo; Takayanagi, Takehiko; Forrester, Steven J.; Preston, Kyle J.; Obama, Takashi; Tsuji, Toshiyuki; Kobayashi, Tomonori; Boyer, Michael J.; Cooper, Hannah A.; Kwok, Hang Fai; Hashimoto, Tomoki; Scalia, Rosario; et al.
Abstract : Angiotensin II (AngII)–activated epidermal growth factor receptor has been implicated in abdominal aortic aneurysm (AAA) development. In vascular smooth muscle cells (VSMCs), AngII activates epidermal growth factor receptor via a metalloproteinase, ADAM17 (a disintegrin and metalloproteinase domain 17). We hypothesized that AngII-dependent AAA development would be prevented in mice lacking ADAM17 in VSMCs. To test this concept, control and VSMC ADAM17-deficient mice were cotreated with AngII and a lysyl oxidase inhibitor, β-aminopropionitrile, to induce AAA. We found that 52.4% of control mice did not survive because of aortic rupture. All other surviving control mice developed AAA and demonstrated enhanced expression of ADAM17 in the AAA lesions. In contrast, all AngII and β-aminopropionitrile-treated VSMC ADAM17-deficient mice survived and showed reduction in external/internal diameters (51%/28%, respectively). VSMC ADAM17 deficiency was associated with lack of epidermal growth factor receptor activation, interleukin-6 induction, endoplasmic reticulum/oxidative stress, and matrix deposition in the abdominal aorta of treated mice. However, both VSMC ADAM17-deficient and control mice treated with AngII and β-aminopropionitrile developed comparable levels of hypertension. Treatment of C57Bl/6 mice with an ADAM17 inhibitory antibody but not with control IgG also prevented AAA development. In conclusion, VSMC ADAM17 silencing or systemic ADAM17 inhibition seems to protect mice from AAA formation. The mechanism seems to involve suppression of epidermal growth factor receptor activation. Abstract : Supplemental Digital Content is available in the text.